Transhumanismus als Beispielthema ludischer Wissenschaftsverhandlung - Rudolf Thomas Inderst (IU Internationale Hochschule, 2022)
– Science and research are labeled as significant producers of knowledge. At the same time, they form and build up socio-cultural everyday knowledge. This type of knowledge is transcending into popular culture - therefore it can also be found in digital games as an integral part of global media culture. The present article takes critical aim at the representation and negotiation of science, research and technology in selected video and computer games. The phenomenon of transhumanism as a techno-ethical as well as ludic discourse field will be at the center of the discussion
Keywords: 790; Game Studies; Transhumanismus; Wissenschaftsgeschichte; Body Enhancement; Körperoptimierung